Superoxide dismutase Ameliorates the Bowel Alterations Induced by diabetes Mellitus – An Experimental Study - Fillmann, Henrique; Tieppo, Juliana; Filho, Nélson Alexandre Kretzmann; Rodrigues, Graziella; Picada, Jaqueline Nascimento; Panés, Julian; Marroni, Norma Possa (Free Radicals and Antioxidants)
Introduction: The gastrointestinal system is frequently affected in patients with diabetes mellitus (DM). Some of these alterations are due to oxidative stress and the production of free radicals. The present study was designed to evaluate whether treatment with superoxide dismutase (SOD) exerts protection on established bowel alterations in experimental diabetes mellitus induced by streptozotocin. We measured the lipid peroxidation, the superoxide dismutase activity and the DNA damage. Materials and Methods: We used the anorectal pressure to evaluate the nitrosative stress and used an inflammatory score to measure the macroscopic and microscopic bowel alterations. Results: The oxidative stress and the DNA damage was elevated in DM group and reduced with the SOD administration. The use of SOD also ameliorates the inflammatory bowel alterations and the anorectal pressure. Conclusion: SOD administration showed beneficial effects in all parameters of large bowel alterations in DM rats.
Keywords: oxidative stress; diabetes; superoxide dismutase